2011
DOI: 10.1523/jneurosci.0858-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Cortical Impact Traumatic Brain Injury in 3xTg-AD Mice Causes Acute Intra-Axonal Amyloid-  Accumulation and Independently Accelerates the Development of Tau Abnormalities

Abstract: Alzheimer’s disease (AD) is a neurodegenerative disorder characterized pathologically by progressive neuronal loss, extracellular plaques containing the amyloid-β (Aβ) peptides, and neurofibrillary tangles composed of hyperphosphorylated tau proteins. Aβ is thought to act upstream of tau, affecting its phosphorylation and therefore aggregation state. One of the major risk factors for AD is traumatic brain injury (TBI). Acute intra-axonal Aβ and diffuse extracellular plaques occur in approximately 30% of human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
188
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 234 publications
(200 citation statements)
references
References 80 publications
11
188
1
Order By: Relevance
“…This rationale also holds true for the lack of an increase in Ab, or a shift in solubility of Ab, after 30 rmTBIs. We, and others, have previously shown that the abnormal production of Ab after TBI occurs at sites of axonal injury, 23,59,62 and in the absence of APP-positive varicosities, it is unlikely that Ab is being produced in higher amounts in our 3xTg-AD mice.…”
Section: Rmtbi Does Not Induce Amyloid or Tau Pathology In 3xtg-ad Micementioning
confidence: 73%
See 2 more Smart Citations
“…This rationale also holds true for the lack of an increase in Ab, or a shift in solubility of Ab, after 30 rmTBIs. We, and others, have previously shown that the abnormal production of Ab after TBI occurs at sites of axonal injury, 23,59,62 and in the absence of APP-positive varicosities, it is unlikely that Ab is being produced in higher amounts in our 3xTg-AD mice.…”
Section: Rmtbi Does Not Induce Amyloid or Tau Pathology In 3xtg-ad Micementioning
confidence: 73%
“…However, multiple groups, including ours, have reported acute increases in phosphorylated (phospho-tau) epitopes after a single TBI, including after controlled cortical impact in tau transgenic mice 58,59 and blast injury in wild-type mice. 60 Chronic hyperphosphorylation of tau has been reported at a single tau epitope in APP transgenic mice at 3 months after closed-head injury.…”
Section: Rmtbi Does Not Induce Amyloid or Tau Pathology In 3xtg-ad Micementioning
confidence: 74%
See 1 more Smart Citation
“…This is common to preclinical mTBI models, as mTBI‐dependent tau pathology has been difficult to model 48. This could be due to differences in injury models,49 injury severity,50 injury frequency,15 age51 at exposure, species used (pig, rat, mice, gerbil), and genetic background (e.g., whether the animal is expressing wild type or human (or mutant) tau or amyloid). In a recent review, we discussed the current literature and the difficulties and challenges of developing in vivo TBI experimental paradigms to explore the link between repetitive head trauma with a focus on tau‐dependent changes 48.…”
Section: Discussionmentioning
confidence: 99%
“…The optical fractionator technique was used to count a systematic random sample of positively-stained axonal varicosities over the entire rostral to caudal extent of the region of interest. Details of these stereological methods have been previously described (Mac Donald et al, 2007a,2007bShitaka et al, 2011;Tran et al, 2011). In brief, for quantification of APP-stained axonal varicosities and Iba1-stained microglia, the region of the corpus callosum and external capsule from each coronal slice was outlined at low power (4 · ), followed by systematic counts of objects of interest at high power (60 · , oil immersion), of sites within the counting region randomly chosen by the StereoInvestigator software.…”
Section: Stereological Quantificationmentioning
confidence: 99%